(untitled) (Sebha University Conference Proceedings, 2024)
This work aims to conduct a practical study between the outcomes of reverse engineering techniques used in redesigning and manufacturing an initial model of the product intended to be manufactured, with linking its results in implementing technical feasibility studies to manufacture products locally instead of importing them. This includes estimating the type and number of manufacturing machines and equipment, calculating the required number of Technicians to operate these machines, and calculate the required raw material quantities, then calculate the total quantities of these variables for the total number of project products targeted to be produced according to the volume of demand for production estimated from previous marketing studies. A technical study was conducted to manufacture an agricultural plow as a case study in this research, and comprehensive studies were conducted on the total quantities of machines, workers number, and raw materials required implementing a line to produce and manufacture them locally. One of the advantages of replacing industries locally is saving foreign exchange for the cost of importing. After applying the reverse engineering technique, collecting their data, measuring their dimensions, preparing detailed drawings for them, manufacturing an initial model locally at the Advanced Center for Mechanical Technology. This study gave encouraging results about the possibility of manufacturing locally for some Products imported from abroad, and all requirements for establishing an integrated production line were calculated and estimated, according to the number targeted to be produced.